Manajemen Program Tahfidz Metode At-Taisir Learning Center di Pondok Damanhuri Romli Pesantren Zainul Hasan Genggong Probolinggo - Sultan Saiful Rijal; Nanang Qosim; M. Fuad Badruddin (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The Al-Qur'an is a holy book that is highly revered in Islam. The Al-Qur'an is also a guide to life that has been designed and compiled by Allah very perfectly to become a guide for the lives of all His followers. There are many glories that Allah promises if we want to keep the Koran, one of which is by memorizing it. Because from the time of Rasulullah, during the process of the gradual revelation of the Qur'an through the Angel Gabriel to Rasulullah Muhammad SAW, the companions maintained its authenticity by memorizing the revealed verses one by one, so that during the time of Caliph Uthman bin Affan, the Qur'an began to be written down. into one mushaf. This is what makes the author very interested in researching the management of the tahfidz program using the at-taisir learning center ALC method at PondokDamanhuriRomliZainulHasanGenggong Islamic Boarding School. The method used in this research is qualitative with a field research type. The data collection techniques used were observation, interviews and document review. The results of research conducted by researchers are; 1) Planning the ALC method tahfidz program starts from dividing time, determining classes and preparing equipment such as mushaf, teachers, places and also cards for deposits. 2) Implementing the ACL method, students memorize one sheet a day and the target is to complete the memorization within two years. 3) However, in the evaluation, this method is actually very good, but the problem is that the students still have a low level of motivation to memorize.